Lęk akulturacyjny cudzoziemców w aspekcie tożsamości i procesów integracyjnych w nowym kraju pobytu - Wallas, Małgorzata (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
Multiculturality and peaceful coexistence has recently become a global issue. A foreigner’s cultural integration in his/her new country of residence may depend on numerous external and internal factors, yet it requires the individual’s personal involvement. The liberal law of the host country will hardly be helpful if the foreigners do not exert their own effort in the course of the acculturation process. Ahigh level of self-awareness allows them to use the stress of acculturation and its consequences in a way that is advantageous to their own creative development, even if the individuals concerned display anxiety, thus resulting in the self-transformation of an individual’s cultural identity. The level of acculturation anxiety produces defined emotional and behavioral outcomes in aliens, while it implies various forms of cultural integration: from its absence, through illusionary integration, passive and active integration, to full integration. Despite the clash of cultural differences and intensified acculturation stress, setting up a bi-cultural family induces self-transformation and integration with the new culture to a larger extent than in the case of single persons. Owing to the internal change of the value system, a foreigner develops a bi-cultural identity. Bi-cultural relations give their members the sense of belonging to a new cultural group, ensure the development of inter-cultural competence in the form of norms, rules and rituals, which increases the degree of mutual trust, tolerance and the sense of security, thus allowing them to achieve higher acculturation efficiency.